Keefektifan Pembelajaran Menulis Cerpen dengan Model Project Based Learning dan Model Sinektik yang Bermuatan Nilai-Nilai Anti-Bullying bagi Siswa Kelas VIII SMP Negeri 8 Semarang - Dian Nugraheni; Zuliyanti Zuliyanti (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effectiveness of teaching short story writing using the Project-Based Learning (PjBL) model and the Synectics model, both of which incorporate anti-bullying values, and to compare the effectiveness of the two. The study employed a quantitative approach using a nonequivalent control group design with eighth-grade students at SMP Negeri 8 Semarang, with two classes as the sample: Class VIII A (PjBL) and Class VIII B (Synectics). Data were collected through pretests, posttests, and observations, then analyzed using normality tests, homogeneity tests, Paired Sample t-tests, N-Gain, and Independent Sample t-tests. The results showed that the average N-Gain score for the PjBL model was 59.17% and for the Synectics model was 61.50%, both falling into the moderate category (moderately effective). The Independent Sample t-test showed no significant difference between the two models (Sig. 0.661 > 0.05), although the Synectic model was slightly superior by a margin of 2.33%. Thus, both learning models are equally effective and have comparable levels of effectiveness; however, the Synectics learning model outperforms the PjBL model in terms of N-gain percentage for teaching short story writing with anti-bullying themes